PENGELOLAAN KERAGAMAN SUMBER DAYA MANUSIA: DIVERSITY-RELATED ORGANIZATIONAL OUTCOMES - Damayanti, Nurul Ashtri (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2003)
Organizational structure, tasks, and reward influence the activation of personal, relational, ann collective identity outcomes related to the awareness, influence, and individual behavior of a majority and minority group with inherent individual diversity on the organizational outcomes. Previous researches showed that diversity which was effectively managed could gave significant contribution to increasing human resources quality needed for achieving organizational outcomes according to the organization’s objectives. Conditioning relational identity outcomes would be able to give benefits and lessen shortages related to diversity.Keywords: organizational outcomes, competitive advantage, performance, team work